Evaluation of LI-RADS Version 2018 Treatment Response Algorithm for Hepatocellular Carcinoma in Liver Transplant Candidates: Intraindividual Comparison between CT and Hepatobiliary Agent–enhanced MRI - Bae, Jae Seok; Lee, Jeong Min; Yoon, Jeong Hee; Kang, Hyo-jin; Jeon, Sun Kyung; Joo, Ijin; Lee, Kyoung Bun; Kim, Haeryoung (Radiology, 2021)
Background The Liver Imaging Reporting and Data System (LI-RADS), version 2018, treatment response algorithm (TRA) is used to assess hepatocellular carcinoma (HCC) after local-regional therapy (LRT). However, its diagnostic performance has not yet been fully compared between CT and hepatobiliary agent (HBA)-enhanced MRI in patients who have undergone liver transplant (LT). Purpose To compare the diagnostic performance of LI-RADS TRA when using CT versus using HBA-enhanced MRI in an intraindividual manner according to pathologic results. Materials and Methods Between January 2011 and September 2019, 165 patients with 237 clinically suspected HCCs underwent LRT followed by LT and were retrospectively included. All patients underwent both CT and HBA-enhanced MRI after LRT and before LT. Three radiologists independently assessed tumor viability with both modalities by using LI-RADS TRA and reached a consensus. Pathologic tumor viability categorized as either completely (100%) or incompletely (<100%) necrotic obtained from the explanted liver served as the reference standard. Sensitivity and specificity of the LI-RADS TRA in the consensus reading were then compared between CT and HBA-enhanced MRI by using the ratio estimator approach. Interobserver agreements were calculated by using Fleiss κ statistics. Results There were 165 patients (mean age, 62 years ± 9 [standard deviation]; 135 men) with a total of 237 lesions, of which 107 were viable tumors (45.1%) at pathologic evaluation. With the LI-RADS TRA, sensitivity and specificity of the viable category for detection of viable HCCs at pathologic evaluation were 42.1% (45 of 107 lesions) and 95.4% (124 of 130 lesions) with CT and 52.3% (56 of 107 lesions) and 93.9% (122 of 130 lesions) with HBA-enhanced MRI, with a significant difference in sensitivity but not specificity ( = .009 and = .42, respectively). Interobserver agreements for the LI-RADS TRA were substantial for both CT and HBA-enhanced MRI (κ, 0.69 for both). Conclusion In patients who underwent local-regional therapy for hepatocellular carcinoma before liver transplant, hepatobiliary agent-enhanced MRI was more sensitive than CT in evaluating tumor viability with the Liver Imaging Reporting and Data System, version 2018, treatment response algorithm. ©RSNA, 2021 See also the editorial by Bashir and Mendiratta-Lala in this issue.